COVID-19-Associated Case Fatality Rate in Subjects Under 18 Years Old in Mexico, up to December 31, 2020 - Navarro-Olivos, Efraín; Padilla-Raygoza, Nicolás; Flores-Vargas, Gilberto; Gallardo-Luna, María de Jesús; León-Verdín, Ma Guadalupe; Lara-Lona, Elia; Magos-Vázquez, Francisco J.; Díaz-Martínez, Daniel Alberto (Frontiers in Pediatrics, 2021)
Background. The emergence of the SARS-CoV-2 virus and the COVID-19 have become a global health crisis. The infection has been present in all the social sectors. The subjects under 18 years is one of them. The objective was to analyze the case fatality ratio of COVID-19 cases in the Mexican population under 18 years of age registered in the National Epidemiological Surveillance System from March 2020 to December 31, 2020. Material and Methods. The design is cross-sectional, quantitative, and analytical. For the data analysis, we considered all the registries in the database from the Ministry of Health, including negative and confirmed cases of COVID-19, up to December 31, 2020. All the suspected cases of respiratory viral disease, with an rRT- PCR test result , aged from 0 to 17 years, were included. Descriptive statistics are presented for all the variables. Epidemiological curves were designed. The Chi-squared test and its P-values were obtained to show the relationship between co-morbidities and death. The Case Fatality Ratio was computed for each co-morbidity, sex, and age group. Multivariable logistic regression models were fitted to study the effect between sex and age group with fatality of cases and co-morbidities and death, adjusting for sex and age group as potential confounders. The alpha-value was fixed to .05 to assess significance. Results. The number of records for this study was 167,856. Among them, 48,505 were from SARS-CoV-2 positive patients (28.90%), and 119,351 (71.10%) were negative. Of those who died, males (55.29%) (P <.05) and those under two years of age (50.35%) (P <.05) predominated. Unlike in older populations, the co-morbidities considered risk factors for death by COVID-19 do not show a statistically significant effect on the fatality of cases. Sex and age group were not confounders for the models in those under 18 years old. Pneumonia and hospitalization are related to death. Conclusion. The Case Fatality Ratio in those under 18 years old is low. The co-morbidities considered in the National System of Epidemiological Surveillance database do not show an association with death in this age group. Asthma lost its protective effect on death.